DHODH and cancer: promising prospects to be explored - Zhou, Yue (Cancer Metab, 2021)
Human dihydroorotate dehydrogenase (DHODH) is a flavin-dependent mitochondrial enzyme catalyzing the fourth step in the de novo pyrimidine synthesis pathway. It is originally a target for the treatment of the non-neoplastic diseases involving in rheumatoid arthritis and multiple sclerosis, and is re-emerging as a validated therapeutic target for cancer therapy. In this review, we mainly unravel the biological function of DHODH in tumor progression, including its crucial role in de novo pyrimidine synthesis and mitochondrial respiratory chain in cancer cells. Moreover, various DHODH inhibitors developing in the past decades are also been displayed, and the specific mechanism between DHODH and its additional effects are illustrated. Collectively, we detailly discuss the association between DHODH and tumors in recent years here, and believe it will provide significant evidences and potential strategies for utilizing DHODH as a potential target in preclinical and clinical cancer therapies.